Efficacy and safety of fixed dose combination of arterolane maleate and piperaquine phosphate dispersible tablets in paediatric patients with acute uncomplicated Plasmodium falciparum malaria: a phase II, multicentric, open-label study. (December 2015) - Toure, Offianan; Rulisa, Stephen; Anvikar, Anupkumar; Rao, Ballamudi; Mishra, Pitabas; Jalali, Rajinder; Arora, Sudershan; Roy, Arjun; Saha, Nilanjan; Iyer, Sunil; Sharma, Pradeep; Valecha, Neena
Abstract Background The World Health Organization (WHO) recommends artemisinin combination therapy (ACT) for the treatment of uncomplicatedPlasmodium falciparum malaria. The present study investigated the efficacy and safety of fixed dose combination (FDC) of arterolane maleate 37.5 mg and piperaquine phosphate (PQP) 187.5 mg dispersible tablets in paediatric patients aged 6 months to 12 years. Methods Male and female patients aged 6 months to 12 years who were confirmed cases ofP. falciparum mono-infection with fever or documented history of fever in the previous 24 h were included. The patients were administered FDC of arterolane maleate and PQP as single daily doses for three consecutive days based on their age. The primary efficacy outcome was proportion of patients with polymerase chain reaction (PCR)-corrected adequate clinical and parasitological response (ACPR) on day 28. Safety was analysed based on adverse events (AE), laboratory abnormalities and abnormalities on electrocardiograph. Results A total of 141 eligible paediatric patients received FDC of arterolane maleate and PQP in a 42-day follow-up study. All the enrolled patients (141) were included in intention to treat (ITT) and safety analyses, and 126 patients were considered in per protocol (PP) population. The PCR-corrected ACPR on day 28 was achieved in all patients (100 %; 95 % CI 97.11–100) included in PP population. The median parasite clearance time (PCT) and fever clearance time (FCT) were 24 h (95 % CI 18.0–24.0) and 10 h (95 % CI 4.0–18.0), respectively. The most frequently reported clinical AE was vomiting. Majority of the AEs were mild to moderate in severity and resolved without sequelae. No patient was discontinued for any QTc (corrected QT interval) prolongation. No deaths or serious AEs were reported during the study. Conclusion The findings from this study showed that FDC of arterolane maleate and PQP effectively curesP. falciparum malaria and attains acceptable level of cure by day 28 in paediatric patients. The efficacy and safety results observed in children warrants further studies on FDC of arterolane maleate and PQP dispersible tablets. Trial Registration: Clinical Trial Registry India: CTRI/2009/091/000531